If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -4 = 2x + 14 Reorder the terms: -4 + 4x = 2x + 14 Reorder the terms: -4 + 4x = 14 + 2x Solving -4 + 4x = 14 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 4x + -2x = 14 + 2x + -2x Combine like terms: 4x + -2x = 2x -4 + 2x = 14 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 2x = 14 + 0 -4 + 2x = 14 Add '4' to each side of the equation. -4 + 4 + 2x = 14 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = 14 + 4 2x = 14 + 4 Combine like terms: 14 + 4 = 18 2x = 18 Divide each side by '2'. x = 9 Simplifying x = 9
| 1/3+2x=5/12 | | 8X-5Y-3=0 | | 50=9x+5 | | 3(2x-1)=2(4x-7) | | 0.3x+33.6=51 | | 7x-10=x+2 | | 7.3x-5.8+2.5x= | | F(x)=2x^2+5x+9 | | 56=24(1/6z+5/6) | | 8x=27-x | | H=-16t^2+72t+3 | | -38.5=4.3z-4.1 | | 2x+4-3x=9 | | 24-2x=-6x+4 | | 2x+6-5x=-3 | | 3.1=1.3+2.9 | | 16=20(1/5z+4/5) | | H=-16t+72t+3 | | 5x+2-3x=-2 | | (X+4)(5x-1)=0 | | 3x+6-4x=8 | | a^2=135+6a | | 3x+4-2x=9 | | 38x-13=5(7x-1)+3x-8 | | -6x=-4x-16 | | (x+3)(x+6)+(x+3)(x+6)= | | 3x-5-6x=4 | | 7(z+3)-5z=9 | | 5(5-y)/3=y | | Y^2/30=y/15+1/2 | | 5x-8-6x=-7 | | -5(4x-7)+3=-20x+38 |